GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2018)
A dataset containing 847 species occurrences available in GBIF matching the query: Country: Brazil or Colombia or Ecuador or Peru or Bolivia, Plurinational State of or Chile or Venezuela, Bolivarian Republic of or Argentina HasCoordinate: true TaxonKey: Parablechnum cordatum (Desv.) Gasper & Salino HasGeospatialIssue: false. The dataset includes 847 records from 75 constituent datasets: 9 records from DAV UC Davis Center for Plant Diversity. 2 records from iNaturalist Research-grade Observations. 3 records from HEPH - Herbário Ezechias Paulo Heringer. 64 records from FURB - Herbário Dr. Roberto Miguel Klein. 38 records from The New York Botanical Garden Herbarium (NY). 5 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 3 records from SANT Herbarium vascular plants collection. 2 records from ALCB - Herbário Alexandre Leal Costa. 11 records from CESJ - Herbário Leopoldo Krieger. 4 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 90 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 1 records from HVAT - Herbário do Vale do Taquari. 18 records from MBML-Herbario - Herbário Mello Leitão. 6 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 2 records from SPF - Herbário da Universidade de São Paulo. 14 records from HUCS - Herbário da Universidade de Caxias do Sul. 5 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 1 records from SPSF - Herbário Dom Bento José Pickel. 2 records from Colección general del plantas vasculares del Herbario JBB. 1 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 7 records from PACA-AGP - Herbarium Anchieta. 2 records from Herbario Pontificia Universidad Javeriana. 1 records from Registros de plantas obtenidos en el monitoreo de una de las plataformas instaladas por CORNARE en Antioquia. 18 records from NMNH Extant Specimen Records. 5 records from Royal Botanic Garden Edinburgh Herbarium (E). 37 records from ICN - Universidad Nacional de Colombia. 3 records from CSIC-Real Jardín Botánico-Colección de Plantas Vasculares (MA). 11 records from Helechos de la jurisdicción de Corantioquia. 2 records from Colección del Herbario PSO de la Universidad de Nariño. 2 records from HUSC - Herbário Unisanta. 1 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 19 records from Herbario Nacional Colombiano (COL). 15 records from Estudios bióticos: Plantas, anfibios, mamíferos, aves y edafofauna epígea (coleópteros y arácnidos), en el complejo de páramo Los Nevados. 1 records from IAC - Herbário do Instituto Agronômico de Campinas. 1 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 1 records from Lund Botanical Museum (LD). 5 records from Natural History Museum (London) Collection Specimens. 7 records from UB - Herbário da Universidade de Brasília. 6 records from Naturalis Biodiversity Center (NL) - Botany. 1 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 2 records from FCAB - Herbário Friburguense. 3 records from UFG - Herbário da Universidade Federal de Goiás. 1 records from HAS - Herbário Alarich Rudolf Holger Schultz. 1 records from IRAI - Herbário do Parque da Ciência Newton Freire Maia. 1 records from HURB - Herbário do Recôncavo da Bahia. 31 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 1 records from BOTU - Herbário Irina Delanova Gemtchújnicov. 8 records from Herbario Universidad de Caldas - FAUC. 3 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 1 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Guantiva - La Rusia. 175 records from Tropicos Specimen Data. 1 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 10 records from Colección Herbario Federico Medem Bogotá - FMB. 3 records from CRI - Herbário Pe. Dr. Raulino Reitz. 5 records from MBM - Herbário do Museu Botânico Municipal. 2 records from Herbario CDMB - Jardín Botánico Eloy Valenzuela. 1 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Vascular Plants National Collection (BAv). 7 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Chiles-Cumbal, La Cocha-Patascoy y Doña Juana Chimayoy.. 21 records from UPCB - Herbário do Departamento de Botânica. 40 records from BHCB-SL - Herbário UFMG - Samambaias e Licófitas. 42 records from Field Museum of Natural History (Botany) Pteridophyte Collection. 2 records from Recopilación de Información de FLORA en la Jurisdicción de CORNARE, hasta el año 2015. 3 records from Australia's Virtual Herbarium. 4 records from Herbario Amazónico Colombiano. 2 records from HUFU - Herbarium Uberlandense. 6 records from UEC - Herbário da Universidade Estadual de Campinas. 1 records from Phanerogamic Botanical Collections (S). 4 records from FUEL - Herbário da Universidade Estadual de Londrina. 14 records from The AAU Herbarium Database. 2 records from naturgucker. 1 records from HJ - Herbario Jataiense Prof. Germano Guarim Neto. 1 records from ANTARCTIC PLANT DATABASE. 17 records from Instituto de Botánica Darwinion. 4 records from ICN - Herbário do Instituto de Ciências Naturais. 1 records from R - Herbário do Museu Nacional. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences